Факторный анализ развития наукоемких производств в региональном аспекте (Путеводитель предпринимателя, 2020)
The level of economic development of the states in XXI century is defined with scientific & technical progress and intellectualization of major manufacture factors: in a global economic competition that countries win which will provide favorable conditions for scientific researches and scientific & technical development. Analysis special the modern condition of high technology manufactures it is necessary look at the aggregate inside and outward factors, which describe the level of development